Aberrant DNA methylation impacts gene expression and prognosis in breast cancer subtypes - Győrffy, Balázs; Bottai, Giulia; Fleischer, Thomas; Munkácsy, Gyöngyi; Budczies, Jan; Paladini, Laura; Børresen‐Dale, Anne‐Lise; Kristensen, Vessela N.; Santarpia, Libero (International journal of cancer, 2016)
DNA methylation has a substantial impact on gene expression, affecting the prognosis of breast cancer (BC) patients dependent on molecular subtypes. In this study, we investigated the prognostic relevance of the expression of genes reported as aberrantly methylated, and the link between gene expression and DNA methylation in BC subtypes. The prognostic value of the expression of 144 aberrantly methylated genes was evaluated in ER+/HER2−, HER2+, and ER−/HER2− molecular BC subtypes, in a meta‐analysis of two large transcriptomic cohorts of BC patients (n = 1,938 and n = 1,640). The correlation between gene expression and DNA methylation in distinct gene regions was also investigated in an independent dataset of 104 BCs. Survival and Pearson correlation analyses were computed for each gene separately. The expression of 48 genes was significantly associated with BC prognosis (p < 0.05), and 32 of these prognostic genes exhibited a direct expression–methylation correlation. The expression of several immune‐related genes, including CD3D and HLA‐A, was associated with both relapse‐free survival (HR = 0.42, p = 3.5E‐06; HR = 0.35, p = 1.7E‐08) and overall survival (HR = 0.50, p = 5.5E‐04; HR = 0.68, p = 4.5E‐02) in ER‐/HER2‐ BCs. On the overall, the distribution of both positive and negative expression–methylation correlation in distinct gene regions have different effects on gene expression and prognosis in BC subtypes. This large‐scale meta‐analysis allowed the identification of several genes consistently associated with prognosis, whose DNA methylation could represent a promising biomarker for prognostication and clinical stratification of patients with distinct BC subtypes. What's new? DNA methylation profiles may play an important role in the development and progression of breast cancer (BC) subtypes, but the prognostic value of aberrantly methylated biomarkers in distinct subtypes and the role of DNA methylation in distinct gene regions remain controversial. This study assesses the prognostic impact of the expression of aberrantly methylated genes and expression–methylation correlations in BC subtypes. Key methylated prognostic genes were identified, including immune‐related genes, particularly in ER−/HER2− tumors. DNA methylation in specific gene regions differentially affects gene expression, supporting the importance of epigenetic biomarkers for prognostication and clinical stratification of patients with distinct BC subtypes.